1991
DOI: 10.1302/0301-620x.73b1.1991785
|View full text |Cite
|
Sign up to set email alerts
|

Modern splinting bandages

Abstract: We have assessed the current range of synthetic splinting bandages, using physical and mechanical tests and the subjective opinions of patients, volunteers and orthopaedic staff. Modern bandages have some better properties than standard plaster bandage but do not conform as well, are more expensive, and potentially more hazardous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Plaster of Paris (gypsum) bandage is a widely used orthopedic splinting material because of its good casting properties and low cost. In some specific situations this material can be used for the treatment of acute fractures and also correction splints [12][13][14][15][16] . Colditz 17 reviewed the importance of plaster of Paris as a material used for making mobilization orthoses.…”
Section: Introductionmentioning
confidence: 99%
“…Plaster of Paris (gypsum) bandage is a widely used orthopedic splinting material because of its good casting properties and low cost. In some specific situations this material can be used for the treatment of acute fractures and also correction splints [12][13][14][15][16] . Colditz 17 reviewed the importance of plaster of Paris as a material used for making mobilization orthoses.…”
Section: Introductionmentioning
confidence: 99%
“…Bodies of Evidence (BoEs) were made and divided into two groups: plates and cylinders. BoEs were made by following the procedures as described in literature (2,5,6,7) , simulating clinical application. For performing standardized BoEs, the development of a matrix specific to each group was required.…”
Section: Methodsmentioning
confidence: 99%
“…For Tribuzi (4) , the use of cast is very efficient, particularly for static serial orthosis manufacturing. Wytch et al (2) found in their study that the incidence of broken plastered orthosis is a matter of concern. Thus, knowing materials properties and manipulation techniques is of major importance to orthosis and prosthesis manufacturing (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations